Japanese horror cinema and Deleuze interrogating and reconceptualizing dominant modes of thought - Barraclough, Rachel Elizabeth (Bloomsbury Academic, 2022)
"Using theories of national, transnational and world cinema, and genre theories and psychoanlaysis as the basis of its argument, Japanese Horror Cinema and Deleuze argues that these understandings of Japanese horror films can be extended in new ways through the philosophy of Deleuze. In particular, the complexities and nuances of how films like Ju-On: The Grudge (2002), Audition (1999) and Kairo (2001) (and beyond) form dynamic, transformative global networks between industries, directors and audiences can be considered. Furthermore, understandings of how key horror tropes and motifs apply to these films (and others more broadly), such as the idea of the "monstrous-feminine", can be transformed, allowing these models to become more flexible."